A Qualitative Study on Risk of Statelessness Among Indigenous Communities in Sarawak, Malaysia: Some Preliminary Findings - Dayang Hajyrayati, Awg Kassim; Noor 'Azlan, Mohd Noor (Research and Scientific Innovation Society, 2024)
This qualitative study examines the risk of statelessness among indigenous communities in Sarawak, exploring both the perspectives of stateless persons and relevant stakeholders. The primary aim is to identify the barriers that contribute to the risk of statelessness and to determine the populations most vulnerable to this condition in Sarawak context. Through in-depth interviews and thematic analysis, the research identifies five barriers that heighten the risk of statelessness among indigenous communities: access barriers, administrative barriers, institutional barriers, behavioural barriers, and financial barriers. The study further classifies those at risk into two categories: those who are undocumented and those possessing some form of documents but lack full citizenship rights. The undocumented population encounters substantial obstacles as a result of their overall lack of legal recognition, which greatly restricts their ability to obtain necessary services and legal safeguards. Meanwhile, those who are documented but lack of citizenship rights experiences a precarious legal status that deprives them of the full rights and protections afforded to citizens. This study highlights the critical importance of policy interventions that tackle the systemic and procedural barriers indigenous populations of Sarawak experience in their acquisition of citizenship. In addition to tackling the immediate bureaucratic obstacles, effective solutions must also consider the sociocultural and legal issues that cause the statelessness condition.